Complex Versus Simple Ankle Movement Training in Stroke Using Telerehabilitation: A Randomized Controlled Trial. - Deng, Huiqiong; Durfee, William K.; Nuckley, David J.; Rheude, Brandon S.; Severson, Amy E.; Skluzacek, Katie M.; Spindler, Kristen K.; Davey, Cynthia S.; Carey, James R. (Physical Therapy, 2012)
Background. Telerehabilitation allows rehabilitative training to continue remotely after discharge from acute care and can include complex tasks known to create rich conditions for neural change. Objectives. The purposes of this study were: (1) to explore the feasibility of using telerehabilitation to improve ankle dorsiflexion during the swing phase of gait in people with stroke and (2) to compare complex versus simple movements of the ankle in promoting behavioral change and brain reorganization. Design. This study was a pilot randomized controlled trial. Setting. Training was done in the participant's home. Testing was done in separate research labs involving functional magnetic resonance imaging (fMRI) and multi-camera gait analysis. Patients. Sixteen participants with chronic stroke and impaired ankle dorsiflexion were assigned randomly to receive 4 weeks of telerehabilitation of the paretic ankle. Intervention. Participants received either computerized complex movement training (track group) or simple movement training (move group). Measurements. Behavioral changes were measured with the 10-m walk test and gait analysis using a motion capture system. Brain reorganization was measured with ankle tracking during fMRI. Results. Dorsiflexion during gait was significantly larger in the track group compared with the move group. For fMRI, although the volume, percent volume, and intensity of cortical activation failed to show significant changes, the frequency count of the number of participants showing an increase versus a decrease in these values from pretest to posttest measurements was significantly different between the 2 groups, with the track group decreasing and the move group increasing. Limitations. Limitations of this study were that no follow-up test was conducted and that a small sample size was used. Conclusions. The results suggest that telerehabilitation, emphasizing complex task training with the paretic limb, is feasible and can be effective in promoting further dorsiflexion in people with chronic stroke.